Research on Drilling Well Control Risk Evaluation Method Based on AHP - Entropy Weight Method - Luo, Jun; Wang, Yong; Liu, Can (Scientific Journal of Technology, 2025)
In order to improve the accuracy and reliability of drilling well control risk evaluation, the study proposes a comprehensive evaluation model based on hierarchical analysis method (AHP) and entropy weight method. By integrating subjective experience and objective data, an index system covering five major criteria layers, namely, environment, human, equipment, management and technology, is constructed, 23 specific indexes are refined, and quantitative grading standards are formulated. AHP is used to determine the subjective weights of each index, entropy weighting method is used to calculate the objective weights, and linear combination method is used to integrate the subjective and objective weights, and finally fuzzy comprehensive evaluation method is used to quantify the risk level. Example analysis shows that formation stability index (0.1345), key equipment failure rate (0.1060) and formation pore pressure change rate (0.1040) are the top three core risk factors, and the results of well control safety evaluation of a drilling project belongs to the “comparatively safe” level. The study shows that this method can effectively balance the subjective and objective factors, clarify the key risk control points, provide theoretical basis and practical guidance for the scientific management of well control risk in drilling projects, and suggests focusing on the monitoring of formation stability, equipment maintenance, and pore pressure dynamic analysis to reduce the probability of well control accidents.